Rheological stability of carbomer in hydroalcoholic gels: Influence of alcohol type. (2nd December 2021) - Kolman, Mackenzie; Smith, Connor; Chakrabarty, Debojit; Amin, Samiul
Abstract: Objective: The main objective of this paper is to analyse and attempt to understand the nature of rheological changes observed and the dynamics of Carbopol NF 980 hydroalcoholic gels neutralized specifically by triethanol amine (TEA), both as a function of time and alcohol type to probe time stabilities and ageing effects in such carbopol gel systems. The rheological changes and dynamics of 3 carbopol gel systems were observed; the gels included a water‐based, ethanol‐based, and isopropyl alcohol‐based gel. It is hoped that this study shall shed light on the dynamical nature and the microstructural evolution of such networked gel systems, which were maintained under closed isothermal conditions and left completely unperturbed. The experimental results can provide the information necessary to understand and proposes plausible mechanisms guiding this dynamical behaviour in hydroalcoholic carbopol gels. Methods: A TA instrument mechanical rheometer was used to measure the viscosity and storage and loss modulus, and a pH meter was utilized to determine the changes in each sample over the period. Results: Studying the differences in the gel structures upon initial preparation illustrated that the ethanol and isopropyl alcohol (IPA) gels differed from the water‐based gel in terms of viscosity, G′, and G″, with the IPA gel displaying the lowest viscosity and moduli values across all shear rates. All the three gel systems exhibited strong shear thinning characteristics and were reminiscent of yield stress type found in colloidal gels. The water‐based gel compared to the hydroalcoholic gels was strongly G′ dominated, with the magnitude of the difference between G′ and G″ observed to be much higher. This reflects that initial formation of the water‐based gel structure possesses a much more rigid structure with a high elastic modulus component dominating. This also suggests that the water‐based gel structure displayed stronger interactions between the carbopol particles when compared to those of the hydroalcoholic gels. Over the 30‐day period, it was observed that the ethanol and water‐based gels did not reveal any appreciable viscosity changes, with only an approximate 12% and 7% change from day 1 to 30, respectively. It was observed that the IPA systems' viscosity drastically increased over the period, with an approximately 77% change from day 1 to 30. The water and ethanol‐based gels also exhibited very similar rheological behaviour over the entire time period with G′ dominating G″. The G″ values of the water and ethanol‐based gels decreased slightly at the end of day 30 by 10% and 16%, respectively, while the G′ values for each sample remained essentially unchanged, increasing only 0.06% for the water‐based gel, and increasing 1.4% for the ethanol‐based gel. This further confirms the relatively stable gel structures attained. For the isopropyl gel system, the storage modulus of the system exhibited an average percent increase of approximately 16% from day 1 to day 30, but interestingly the loss modulus varied the least amongst all the gel systems, with only a 3% increase. The increase in G′ reflects upon the evolution of a more rigid structure by day 30 for the IPA gel. This observation is clearly consistent with the corresponding increase in viscosity observed in the IPA gel. None of the gels tested displayed a consistent pH over the period. The pH of the hydroalcoholic gels was higher than that of the water‐based gel for a majority of the period. The greatest fluctuations in pH were observed for the water and IPA gels, even though the water‐based gel had one of the most stable rheological profiles out of the samples tested. The water, ethanol, and IPA gels' pH increased approximately 25%, 6%, and 5%, respectively, from day 1 to day 30. Conclusion: The rheological and pH study of the 3 hand sanitizer systems over a 30‐day period allowed for rational insights into the plausible reasons responsible for driving the observed rheological changes in these unperturbed systems. For the water‐based gel, we hypothesize that the changes observed are due to physical ageing, where the gel structure has evolved over time to eventually progress towards a more stabilized framework structure. The pH of the gel upon formation was on the lower side. Such a lower pH influences the formation of a gel, which is comparatively less swollen and occupies a slightly lesser volume, and thereby points to a much less compacted gel network structure or alternatively, a more fluid structure. If the particles moved around more, the system was not initially in a state of low energy, causing increased particle movement, and in turn, physical ageing. This could be responsible for the development of a physically altered structure over time. The gel structure dynamically attempts to minimize its free energy by becoming more rigid, which has been observed as being manifested in the decrease of both the viscosity and the G″. For the hydroalcoholic gels, we conjecture that ageing observed was a result of chemical ageing, and the alcohol type employed in the preparation is primarily responsible for exhibiting this effect. The polarities of ethyl alcohol and isopropyl alcohol are key to the stabilization of such resultant network structures which get formed because of neutralization. It has been observed in previous studies that with decreasing polarity, there was an increase in the neutralization needed to obtain the development of a structure half as well developed as the final resultant structure. Isopropyl alcohol is a much less polar solvent compared to ethanol and water, and therefore required higher levels of TEA as the base to neutralize the system. We conjecture that the charged TEA cationic species had a greater propensity to get exchanged with bulk solution in the vicinity of the polymer into the bulk solution, and that the pH fluctuation observed indicated a kinetic exchange process over time, causing the viscosity and moduli profiles to increase along with the pH. At this time though, further investigations need to be carried out to truly understand the underlying instability, and thus dynamics for gel systems of this type. Abstract : This study was carried out to gain insights into factors influencing rheological changes and dynamics of Carbopol NF 980 based hydroalcoholic gels formed by employing Triethanol amine (TEA) as a base during preparation. Extensive rheological studies were conducted to gain deeper insights into viscosity and viscoelastic moduli variations observed in carbomer gels over time. Résumé: Objectif: L'objectif principal de cet article est d'analyser et de tenter de comprendre la nature des changements rhéologiques observés et la dynamique des gels hydroalcooliques Carbopol NF 980 neutralisés spécifiquement par l'amine triéthanol (TEA), à la fois en fonction du temps et du type d'alcool pour sonder les stabilités temporelles et les effets du vieillissement dans de tels systèmes de gel carbopol. Les changements rhéologiques et la dynamique de 3 systèmes de gel de carbopol ont été observés ; les gels comprenaient un gel à base d'eau, d'éthanol et d'alcool isopropylique. On espère que cette étude éclairera la nature dynamique et l'évolution microstructurale de ces systèmes de gel en réseau, qui ont été maintenus dans des conditions isothermes fermées et laissés complètement imperturbables. Les résultats expérimentaux peuvent fournir les informations nécessaires pour comprendre et proposer des mécanismes plausibles guidant ce comportement dynamique dans les gels hydroalcooliques de carbopol. Méthode: Un rhéomètre TA mécanique a été utilisé pour mesurer la viscosité, le module de stockage et de perte, et un pH‐mètre a été utilisé pour déterminer les changements dans chaque échantillon au cours de la période. Résultats: L'étude des différences dans les structures du gel lors de la préparation initiale a montré que les gels d'éthanol et d'alcool isopropylique (IPA) différaient du gel à base d'eau en termes de viscosité, G′ et G'' le gel IPA affichant les valeurs de viscosité et de modules les plus faibles pour tous les taux de cisaillement. Les trois systèmes de gel présentaient de fortes caractéristiques d'amincissement par cisaillement et rappelaient le type de contrainte d'élasticité que l'on trouve dans les gels colloïdaux. Le gel à base d'eau par rapport aux gels hydroalcooliques était fortement dominé par G′, l'ampleur de la différence entre G′ et G'' présentant une importance beaucoup plus élevée. Cela reflète le fait que la formation initiale de la structure de gel à base d'eau possède une structure beaucoup plus rigide avec un composant de module élastique élevé dominant. Cela suggère également que la structure du gel à base d'eau présentait des interactions plus fortes entre les particules de carbopol par rapport à celles des gels hydroalcooliques. Au cours de la période de 30 jours, il a été observé que l'éthanol et les gels à base d'eau n'ont révélé aucun changement de viscosité appréciable, avec seulement un changement approximatif de 12% et 7% du jour 1 au jour 30, respectivement. Il a été observé que la viscosité des systèmes IPA a considérablement augmenté au cours de la période, avec un changement d'environ 77% du jour 1 au jour 30. Les gels à base d'eau et d'éthanol ont également montré un comportement rhéologique très similaire sur toute la période, G′ dominant G''. Les valeurs G'' des gels à base d'eau et d'éthanol ont légèrement diminué à la fin de la journée 30 de 10% et 16%, respectivement, tandis que les valeurs G′ pour chaque échantillon sont restées essentiellement inchangées, n'augmentant que de 0, 06% pour le gel à base d'eau et augmentant de 1, 4% pour le gel à base d'éthanol. Cela confirme en outre les structures de gel relativement stables atteintes. Pour le système de gel isopropylique, le module de stockage du système a montré une augmentation moyenne d'environ 16% du jour 1 au jour 30, mais il est intéressant de noter que le module de perte variait le moins parmi tous les systèmes de gel, avec seulement une augmentation de 3%. L'augmentation de G′ reflète l'évolution d'une structure plus rigide au jour 30 pour le gel IPA. Cette observation est clairement cohérente avec l'augmentation correspondante de la viscosité observée dans le gel IPA. Aucun des gels testés n'a montré un pH constant sur la période. Le pH des gels hydroalcooliques était supérieur à celui du gel à base d'eau pendant la majeure partie de la période. Les plus grandes fluctuations de pH ont été observées pour les gels d'eau et d'IPA, même si le gel à base d'eau avait l'un des profils rhéologiques les plus stables parmi les échantillons testés. Le pH de l'eau, de l'éthanol et des gels IPA a augmenté d'environ 25%, 6% et 5%, respectivement, du jour 1 au jour 30. Conclusion: L'étude rhéologique et pH des 3 systèmes de désinfectant pour les mains sur une période de 30 jours a permis d'obtenir des informations rationnelles sur les raisons plausibles responsables des changements rhéologiques observés dans ces systèmes non perturbés. Pour le gel à base d'eau, nous émettons l'hypothèse que les changements observés sont dus au vieillissement physique, où la structure du gel a évolué au fil du temps pour éventuellement progresser vers une structure plus stabilisée. Le pH du gel lors de la formation était dans la partie inférieure. Un pH aussi bas influence la formation d'un gel, qui est comparativement moins gonflé et occupe un volume légèrement inférieur, et indique ainsi une structure de réseau de gel beaucoup moins compactée ou autrement dit, une structure plus fluide. Si les particules se déplaçaient davantage, le système n'était pas initialement dans un état de faible énergie, ce qui entraînait une augmentation du mouvement des particules et, à son tour, un vieillissement physique. Cela pourrait être responsable du développement d'une structure physiquement modifiée au fil du temps. La structure du gel tente dynamiquement de minimiser son énergie libre en devenant plus rigide, ce qui a été observé comme se manifestant par la diminution de la viscosité et du G'' Pour les gels hydroalcooliques, nous pensons que le vieillissement observé était le résultat d'un vieillissement chimique, et le type d'alcool utilisé dans la préparation est principalement responsable de cet effet. Les polarités de l'alcool éthylique et de l'alcool isopropylique sont essentielles à la stabilisation de ces structures de réseau résultantes qui se forment en raison de la neutralisation. Il a été observé dans des études antérieures qu'avec la diminution de la polarité, il y avait une augmentation de la neutralisation nécessaire pour obtenir le développement d'une structure à moitié aussi bien développée que la structure résultante finale. L'alcool isopropylique est un solvant beaucoup moins polaire que l'éthanol et l'eau, et nécessitait donc des niveaux plus élevés de TEA comme base pour neutraliser le système. Nous pensons que les espèces cationiques TEA chargées avaient une plus grande propension à être échangées avec une solution en vrac à proximité du polymère, dans la solution en vrac, et que la fluctuation du pH observée indiquait un processus d'échange cinétique au fil du temps, entraînant une augmentation des profils de viscosité et de modules avec le pH. À l'heure actuelle, cependant, des recherches supplémentaires doivent être menées pour vraiment comprendre l'instabilité sous‐jacente, et donc la dynamique des systèmes de gel de ce type.